Efisisensi Ekonomi dan Dampak Kebijakan Pemerintah Terhadap Usaha Penangkapan Lemuru di Muncar, Jawa Timur - Mira Mira (Economic Journal of Emerging Markets, 2007)
The objective of this research was analyze economic efficiency and the government policy impact on sardinella Lemuru in Muncar, East Java, in 2007, which are private profitability, social profitability, private cost ratio, domestic cost ratio, nominal protection on output, nominal protection on input, and the government policy economic incentive impact (subsidy ratio to producer, efficiency protection coefficient, and profitability coefficients). The analysis use was policy matrix method. The results indicated private profitability > 0 (683.275.260), it means sardinella Lemuru commodity system get profitability above normal, which have implication that the commodity can be expanded. Social profitability > 0 (144.403.931,4), it means the sardinella Lemuru commodity system more efficient. Private cost ratio < 1 (0,79) indicated the sardinella Lemuru commodity had competitive advantage. Domestic cost ratio < 1 (0,97), it means the sardinella Lemuru commodity had comparative advantage. Nominal protection on output > 1 (1,19), it means the government policy impact on output have beneficial effect to the fisherman, this impact caused sardinella Lemuru price which should be received by fisherman of sardinella Lemuru still a few higher than the sardinella Lemuru exporting price in fisherman levels, sardinella Lemuru price received by farmer 119% from the actual price. Nominal protection on input < 1 (0,97), it means the government policy impacts was input have beneficial effect. The Government policy economic incentive impact value was positive which implicated the government policy given incentive to the fisherman, its caused the profit received was 14 % from the actual price by the fisherman. Keywords: Impact, policy, efficiency, sardinela lemuru